A Path Model to Infer Mathematics Performance: The Interrelated Impact of Motivation, Attitude, Learning Style and Teaching Strategies Variables - Marvin G. Pizon; Shiryl T. Ytoc (East Asian Journal of Multidisciplinary Research, 2022)
The present study aims at exploring predictors influencing mathematics performance. In particular, the study focuses in four subject’s components such as motivation, attitude towards mathematics, learning style, and teaching strategies. A sample of 240 students from Agusan del Sur State College of Agriculture and Technology (ASSCAT) were involved in the study. Path analysis was used to test the direct and indirect relations between the predictors and mathematics performance. Based on the result, the calculation of reproduced correlation through path decompositions and subsequent comparison to the empirical correlation indicated that the path model fits the empirical data. Results also revealed that a large proportion of mathematics performance can be directly predicted from attitude towards mathematics, learning style, and teaching strategies. Moreover, attitude towards mathematics, learning style, and teaching strategies influence mathematics performance in direct and indirect ways.